Games played through agents in the laboratory — a test of Prat & Rustichini's model - Ludwig Ensthaler; Steffen Huck; Johannes Leutgeb (Games and Economic Behavior, 2020)
From the regulation of sports to lawmaking in parliament, in many situations one group of people (“agents”) make decisions that affect the payoffs of others (“principals”) who may offer action-contingent transfers in order to sway the agents' decisions. Prat and Rustichini (2003) characterize pure-strategy equilibria of such Games Played Through Agents. Specifically, they predict the equilibrium outcome in pure strategies to be efficient. We test the theory in a series of experimental treatments with human principals and computerized agents. The theory predicts remarkably well which actions and outcomes are implemented but subjects' transfer offers deviate systematically from equilibrium. We show how quantal response equilibrium accounts for the deviations and test its predictions out of sample. Our results show that quantal response equilibrium is particularly well suited for explaining behavior in such games.
Keywords: D44; C91; D72; D83; 330; games played through agents; experiment; quantal response equilibrium